ENHANCING ADOLESCENT MORAL AWARENESS THROUGH AQIL BALIGH EDUCATION - Wilodati Wilodati; Siti Komariah; Nindita Fajria Utami; Winny Gloria Aritonang; Putri Permata Amir; Putri Hasna Fakhira (Department of Tadris IPS FITK UIN Siber Syekh Nurjati Cirebon, 2024)
There is an imbalance between intellect and maturity; children of the current generation are growing in maturity more than in intellect. This research aims to understand the concept of social deviance and the notion of maturity from the perspective of pre-adolescents, to explore the implementation of maturity education for pre-adolescents, and to identify the efforts made by pre-adolescents to prevent social deviance. The research used a quantitative descriptive method with a survey approach, involving 623 junior high school students aged 11-15 as respondents. The purposive sampling technique is used to select respondents who are considered to have relevant information. Data was collected through a Likert scale-based questionnaire and open-ended questions, then analyzed using percentage techniques. The research results indicate that education for adolescents has a significant impact on reducing the tendency for deviant social behavior among teenagers. A total of 68,65%of teenagers reported performing their religious duties on time, 66,3% are able to distinguish between good and bad, and 65,6% are capable of making the right decisions. Education for adolescents helps teenagers understand religious values, build moral awareness, develop independence, and control emotions, which serve as protective factors against deviant behaviors such as promiscuity, violence, and substance abuse. This research emphasizes the importance of education for adolescents in shaping their character to be socially and individually responsible.Keywords: education, social deviance, aqil puberty